Quality traits in winter wheat: Comparison of stability parameters and correlations between traits regarding their stability. (September 2017) - Knapp, S.; Brabant, C.; Oberforster, M.; Grausgruber, H.; Hiltbrunner, J.
Abstract: Fluctuations of environmental conditions increase variability in both grain yield and quality of wheat ( Triticum aestivum L.). In order to evaluate stability, different stability parameters of the static or the dynamic concept can be applied, which could be negatively correlated. While correlation analysis of the mean performance between traits is common, correlations between stability estimates for quality traits have not been investigated, to the best of the authors' knowledge. Therefore, indirect, rheological and baking traits, and grain yield from two datasets were analysed, and the mean performance, each three stability parameters of the two different concepts (static and dynamic) were calculated over all environments within each dataset. Results showed that stability parameters of the same concept were significantly positively correlated for almost all traits. Between the stability concepts, there was only one significant negative correlation, indicating that no trade-off between the two stability concepts exists. A trade-off between stability and mean performance occurred only for five traits, suggesting only a weak trade-off between stability and mean performance, allowing the development of cultivars that are of both stable and of high quality. Clusters of traits that showed similar stability could be identified but were not consistent across stability parameters and datasets. Highlights: Parameters of same stability concept were correlated and thus are interchangeable. Trade-off between stability concepts only for some traits, allowing improving both. Lack of trade-off between stability parameters and mean allows improving both. Clusters of quality traits regarding their stability detected, but not consistent. Assessment of stability of quality traits needs to be done in several environments.